PERAN PUPUK ORGANIK CAIR URIN KELINCI PADA TANAMAN PAKCOY(Brassica rapa L) - Widyana Rahmatika; Edy Soenyoto; Retno Dwi Andayani; Yunus Susilo (Universitas Tribhuwana Tunggadewi, 2022)
The aimed this study was to determine the effect of rabbit urine liquid organic fertilizer on N uptake, growth, and yield of pakcoy plants and to determine the dose of rabbit urine liquid organic fertilizer on pakcoy plants. This research used a randomized block design which repeated four times. Treatment factor: administration of rabbit urine concentration consisting of 6 treatments: U0 = 0 ml/Plant (Control or no treatment), U1 = 25 ml/Plant, U2 = 30 ml/Plant, U3 = 35 ml/Plant, U4 = 40 ml/ Plant, U5 = 45 ml/ Plant. Two phases of observation parameters were observed in this study, namely the vegetative phase which includes the height of the pakcoy plants in cm units, the number of pakcoy leaves (strands), and the area of the leaves using the length x width times the constant method. The generative phase was observed fresh weight of the plants and the total N uptake at harvest. There are significant differences in the parameters of plant height, number of leaves, and leaf area. Meanwhile, there was no significant difference in the fresh weight of the plants. There were differences in the percentage of nitrogen uptake in each treatment, the highest uptake was in treatment U5, namely using rabbit urine 45 ml/plant, and the lowest in treatment U4, namely using rabbit urine 40 ml/plant.